2018
DOI: 10.5296/bms.v9i2.13615
|View full text |Cite
|
Sign up to set email alerts
|

Customer Experience Marketing (CEM), Customer Satisfaction and Customer Trust Affects Customer Loyalty: A Study on Star Hotels in Jakarta Province

Abstract: This study aims to examine customer experience marketing (CEM), customer satisfaction, consumer trust affects customer loyalty for star hotels in Jakarta, Indonesia. This study employs a causal and descriptive research using a survey research method. This study hypothesizes that (1) CEM has a significant effect on customer loyalty, (2) CEM has a significant effect on customer satisfaction, (3) customer satisfaction has a significant effect on customer loyalty, (4) customer satisfaction has a significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…The researchers further found when consumer satisfaction rises, consumer trust will more increase. It is in accordance with the results of hypothesis testing and research (Elrado, et al, 2014;Trini and Salim, 2018;Wardaya, 2017) that consumer satisfaction has a significant positive effect on consumer trust. Consumers who are satisfied with JNE services will create great trust.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The researchers further found when consumer satisfaction rises, consumer trust will more increase. It is in accordance with the results of hypothesis testing and research (Elrado, et al, 2014;Trini and Salim, 2018;Wardaya, 2017) that consumer satisfaction has a significant positive effect on consumer trust. Consumers who are satisfied with JNE services will create great trust.…”
Section: Discussionsupporting
confidence: 89%
“…When consumers are satisfied with the services provided by the company, they will trust the company. A research study (Trini and Salim, 2018) explains consumer satisfaction has a H 1 : Service quality has a positive and significant effect on consumer satisfaction H 2 : Service quality has a positive and significant effect on consumer trust H 3 : Consumer experience has a positive and significant effect on consumer satisfaction H 4 : Consumer experience has a positive and significant effect on consumer trust…”
mentioning
confidence: 99%
“…This opinion is also in line with the results of research conducted by Leninkumar (2017), which found that customer trust had a significant positive effect on customer loyalty in commercial banks in Sri Lanka. The results of other studies found a significant positive influence between customer trust and customer loyalty, namely Nur (2012), Sarwar et al (2012), Utami (2015), Leninkumar (2017), Trini and Salim (2018), and Widodo and Murwatiningsih (2019). On the other hand, a study conducted by Setiawan and Sayuti (2017) found that customer trust had no significant effect on customer loyalty.…”
Section: Introductionmentioning
confidence: 86%
“…Most businesses excel because they plough back part of their proceeds to the society (Marin Ruiz & Rubio, 2009;Uduji & Okolo-Obasi, 2019). Firms that fail to meet the society's expectations also find it difficult to attract and retain customers from the surrounding community (Aggarwal and Singh, 2019;Cha, Abebe, & Dadanlar, 2019;Trini, & Salim, 2018). Thus, if corporates wish to be viable in the long run, they should respond to needs of the society through involvement in philanthropic programmes (Ahen & Amankwah-Amoah, 2018;Fatma, Khan, & Rahman, 2019).…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%